Arthroscopic Pectoralis Minor Release and Infraclavicular Brachial Plexus Decompression for Neurogenic Thoracic Outlet Syndrome - Eric R. Wagner, MD, MS, FAOA; Thomas J. McQuillan, MD; Oluwakorede Omole, MD; Sameer R. Khawaja, BS; Kevin R. Cuneo, BS; Zaamin B. Hussain, MD, EdM; Hayden L. Cooke, BS; Krishna N. Chopra, MA; Michael B. Gottschalk, MD, FAOA; Robert L. Bowers, DO, PhD (JBJS Open Access)
Background:. Neurogenic thoracic outlet syndrome (nTOS) of infraclavicular etiology is a complex condition involving the compression of the brachial plexus through the interscalene triangle and costoclavicular, infraclavicular, and pectoralis minor space. New insight into nTOS of infraclavicular etiology and its association with scapular dyskinesia has enabled minimally invasive treatments: endoscopic pectoralis minor release (PMR) and infraclavicular brachial plexus neurolysis. The purpose of this study was to analyze clinical outcomes of this technique compared with historically published outcomes for open first rib resection (FRR) and/or scalenectomy. Methods:. All patients who underwent endoscopic surgical decompression for nTOS of infraclavicular etiology were retrospectively reviewed at a single institution. Surgical treatment included endoscopic PMR, subclavius release, and neurolysis of the infraclavicular brachial plexus. Patient-reported outcomes were collected prospectively and compared with prior research on FRR and scalenectomy. A subgroup analysis was performed on patients with prior open FRR or anterior cervical discectomy and fusion (ACDF). Results:. Fifty-eight shoulders among 55 patients were included, with an average follow-up of 25.8 months (range: 12-52). Patients showed significant improvement in visual analog scale pain (7.0-2.1) and single alpha-numeric evaluation scores (37% to 84%). Overall, 90% of patients experienced good or excellent outcomes according to the Derkash classification. There were no major complications and only 2 minor ones (one wound infection and one case of adhesive capsulitis). Satisfaction and Derkash scores among patients undergoing endoscopic surgery were comparable with previously published studies on open FRR and scalenectomy, with lower rates of major complications and equivalent or improved clinical outcomes. Patients with prior ACDF or open FRR had worse postoperative American Shoulder and Elbow Surgeons; Quick Disabilities of the Arm, Shoulder, and Hand; and Derkash scores than the subgroup with no prior intervention. Conclusions:. Endoscopic PMR and infraclavicular brachial plexus decompression is a viable and effective treatment option for nTOS of infraclavicular etiology driven by the pectoralis minor and associated scapular girdle dyskinesia. This cohort demonstrates improvements in clinical outcomes comparable with open scalenectomy and FRR with high patient satisfaction and no major neurologic, vascular, or thoracic complications. Level of Evidence:. Therapeutic Level IV–Case Series. See Instructions for Authors for a complete description of levels of evidence.